Parasite fauna of farmed Nile tilapia (Oreochromis niloticus) and African catfish (Clarias gariepinus) in Uganda - Akoll, Peter; Konecny, Robert; Mwanja, Wilson W.; Nattabi, Juliet K.; Agoe, Catherine; Schiemer, Fritz (Parasitology research, 2012)
An intensive parasite survey was conducted in 2008 to better understand the parasite fauna occurrence, distribution and diversity in the commercial aquaculture fish species in Uganda. A total of 265 fish collected from hatcheries and grow-out systems were examined for parasites using routine parasitological techniques. The survey yielded 17 parasite species: 11 from Oreochromis niloticus and ten from Clarias gariepinus. Four parasites—Amirthalingamia macracantha, Monobothrioides sp., Zoogonoides sp. and a member of the family Amphilinidae—were recorded for the first time in the country. The parasite diversity was similar between hosts; however, O. niloticus was dominated by free-living stage-transmitted parasites in lower numbers, whereas both trophically and free-living stage-transmitted parasites were equally represented in C. gariepinus in relatively high intensities. The patterns in parasite numbers and composition in the two hosts reflect differences in fish habitat use and diet. A shift in parasite composition from monoxenous species-dominated communities in small-sized fish to heteroxenous in large fishes was recorded in both hosts. This was linked to ontogenetic feeding changes and prolonged exposure to parasites. Polyculture systems showed no effect on parasite intensity and composition. The gills were highly parasitized, mainly by protozoans and monogeneans. Generally, the occurrence and diversity of parasites in these fish species highlight the likelihood of disease outbreak in the proposed intensive aquaculture systems. This calls for raising awareness in fish health management among potential farmers, service providers and researchers.
Keywords: Parasite fauna; Farmed Nile tilapia (Oreochromis niloticus); African catfish (Clarias gariepinus)